Occurrences Of Ferromanganese Crusts In The Lemkein Seamount Of RMI: Preliminary Results - Jai-Woon Moon (International Marine Minerals Society, 2000)
Lemkein seamount located in the west of the Kuwajleen Atoll of RMI is a relatively samll, simple-shaped, peaked type seamount with its base at 4,500 m and summit at 1,452 m water depths. Ferromanganese crusts were identified in the water depth range between 2,000 m and 2,500 m, and they were mostly observed on the northern slopes of the seamount. Among various substrate rocks, breccia occurred most commonly with crusts and formed the thickest crust layers. Average thickness of the Lemkein crusts was about 5 cm. Their chemical compositions were similar to other crusts found in the RMI area; Mn=25.82%, Fe=15.29%, Co=0.74%, Ni=0.56%. Lemkein crusts were characterized by their four distinctive internal layers; 1) Massive Layer 1; 2)Porous, Fe-stained or sediment infilled Layer 2; 3) Massive to slightly porous Layer 3; and, 4)Massive, Dense, Phosphotized, CFA veined Layer 4. Layers 1 and 2 were generally similar in composition, but highest Co concentrations were measured in Layer 1 while relatively higher concentrations of Al, Rb, Fe, and Ti were observed in Layer 2. Layer 3 showed higher concentrations of Ca and P than Layers 1 and 2. Based on the Co-chronography, the age of Layer 1 is 0¡?6 Ma (growth rate = 1.50 mm/Ma), Layer 2 is 6¡?15 Ma (1.75 mm/Ma), Layer 3 is 15¡?27Ma (1.76 mm/Ma), and Layer 4 is 27¡?45 Ma (2.06 mm/Ma). These preliminary results indicated that high Co contents in Layer 1 resulted from slow growth rates; Layer 2 was formed under relatively strong influence of high terrestrial input; and, Layer 3 was probably affected by a minor phosphatization event occurring in 15 Ma.